Trends in socioeconomic inequalities in the prevalence of functional dentition among older people in Brazil - Fabiola Bof de Andrade; Jose Leopoldo Ferreira Antunes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
The objective of this research was to evaluate trends in socioeconomic inequalities in the prevalence of functional dentition among community-dwelling older adults in Brazil. This was a cross-sectional study with data from the last two SBBrasil Project surveys conducted in 2003 and 2010. Functional dentition was defined as the presence of 20 or more natural teeth and was assessed during the clinical examination of dentition status. Schooling was used as the socioeconomic position measure. Socioeconomic inequality was measured using two complex measures; the slope index of inequality (SII) and the relative index of inequality (RII). The prevalence of functional dentition was 10.8% (95%CI: 8.1-14.2) in 2003 and 13.6% (95%CI: 11.1-16.5) in 2010. The prevalence of functional dentition increased significantly over the educational rank in both years. Absolute inequalities were significant for both years and remained unaltered between 2003 and 2010. Significant relative inequality in the prevalence of functional dentition was found in both years of the survey. Socioeconomic inequalities in the prevalence of functional dentition among older adults in Brazil persisted significantly between both national oral health surveys.